Effect of azole fungicide mixtures, alternations and dose on azole sensitivity in the wheat pathogen Zymoseptoria tritici. (25th May 2015) - Dooley, H.; Shaw, M. W.; Spink, J.; Kildea, S.
Abstract : The evolution of fungicide resistance in the cereal pathogen Zymoseptoria tritici is a serious threat to the sustainability and profitability of wheat production in Europe. Application of azole fungicides has been shown to affect fitness of Z. tritici variants differentially, so it has been hypothesized that combinations of azoles could slow the evolution of resistance. This work assessed the effects of dose, mixtures and alternations of two azoles on selection for isolates with reduced sensitivity and on disease control. Naturally infected field trials were carried out at six sites across Ireland and the sensitivity of Z. tritici isolates monitored pre‐ and post‐treatment. Epoxiconazole and metconazole were applied as solo products, in alternation with each other, and as a pre‐formulated mixture. Full and half label doses were tested. Isolates were partially cross‐resistant to the two azoles, with a common azole resistance principal component accounting for 75% of the variation between isolates. Selection for isolates with reduced azole sensitivity was correlated with disease control. Decreased doses were related to decreases in sensitivity but the effect was barely significant ( P  =   0·1) and control was reduced. Single applications of an active ingredient (a.i.) caused smaller decreases in sensitivity than double applications. Shifts in sensitivity to the a.i. applied to a plot were greater than to the a.i. not applied, and the decrease in sensitivity was greater to the a.i. applied at the second timing. These results confirm the need to mix a.i.s with different modes of action.